2020
DOI: 10.1109/tmi.2019.2935553
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Pulmonary Nodule Detection in CT Scans Using Convolutional Neural Networks Based on Maximum Intensity Projection

Abstract: Accurate pulmonary nodule detection is a crucial step in lung cancer screening. Computer-aided detection (CAD) systems are not routinely used by radiologists for pulmonary nodule detection in clinical practice despite their potential benefits. Maximum intensity projection (MIP) images improve the detection of pulmonary nodules in radiological evaluation with computed tomography (CT) scans. Inspired by the clinical methodology of radiologists, we aim to explore the feasibility of applying MIP images to improve … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…[31][32][33] We also improve our performance in detection of nodules smaller than 6 mm, compared to our previous work (sensitivity: 93.4% vs. 90.4%, at 1.0 FP/scan; sensitivity: 95.0% vs. 91.6%, at 2.0 FPs/scan). 30 Another study from Ozdemir et al 24 showed a sensitivity of around 90% with 1FP/scan for nodules smaller than 5 mm, whereas our method achieved a sensitivity of 93.0% with 1FP/scan to detect nodules with the same size. Methods of Dou et al, 21 Xie et al, 22 and Huang et al 26 might need to further improve the discrimination between nodules and wrong findings.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[31][32][33] We also improve our performance in detection of nodules smaller than 6 mm, compared to our previous work (sensitivity: 93.4% vs. 90.4%, at 1.0 FP/scan; sensitivity: 95.0% vs. 91.6%, at 2.0 FPs/scan). 30 Another study from Ozdemir et al 24 showed a sensitivity of around 90% with 1FP/scan for nodules smaller than 5 mm, whereas our method achieved a sensitivity of 93.0% with 1FP/scan to detect nodules with the same size. Methods of Dou et al, 21 Xie et al, 22 and Huang et al 26 might need to further improve the discrimination between nodules and wrong findings.…”
Section: Discussionmentioning
confidence: 57%
“…With projected images as input, convolutional neural networks (CNNs) were employed to identify nodule candidates. 30 Nodule cubes with various sizes were extracted for reduction of false positives. The results showed that using maximum intensity projection can improve the performance of deep learning-based CAD for lung nodule detection.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The 24Ɨ24Ɨ4 receptive field encompasses small-sized nodules with proper amount of context. In the fusion stage, contour retrieval and an approximation method [27] are combined to extract and refine the predicted candidate information, such as coordinates and size of the bounding box. For candidates with centers are too close to each other, a distance ratio of 1.1 is used to distinguish whether two candidates are actually one finding or two individual findings.…”
Section: A V-netmentioning
confidence: 99%
“…For pulmonary nodes, such a component is the maximum intensity projection (MIP) image. MIP [20,21] is a postprocessing method that projects 3D voxels with maximum intensity to the projection plane. The advantage of MIP is that its formation is a 2D task and therefore requires less computing resources.…”
Section: Background and Related Workmentioning
confidence: 99%